A road to obstetric fistula in Malawi: capturing women’s perspectives through a framework of three delays - Changole J; Combs Thorsen V; Kafulafula U (Dove Medical Press, 2018)
Josephine Changole,1 Viva Combs Thorsen,1 Ursula Kafulafula2 1Department of Community Medicine and Global Health, University of Oslo, Oslo, Norway; 2Kamuzu College of Nursing, University of Malawi, Blantyre, Malawi Introduction: Obstetric fistula (OF) is a devastating birth injury, which leaves a woman with leaking urine and/or feces accompanied by bad smell, a situation that has been likened to death itself. The condition is caused by neglected obstructed labor. Many factors underlie fistula formation, most of which are preventable. The main purpose of this study was to explore labor and childbirth experiences of women who developed OF with a focus on accessibility of care in the central region of Malawi.Methods: We conducted semi-structured interviews with 25 women with OF at Bwaila Fistula Care Center in Lilongwe and in its surrounding districts. We interviewed 20 women at Bwaila Fistula Care Center; additional five women were identified through snowball sampling and were interviewed in their homes. Data were categorized using Nvivo 11 and were analyzed using thematic analysis. The three delays model by Thaddeus and Maine was used for data analysis.Findings: The majority of women in our study suffered from OF with their subsequent pregnancies. All women experienced delays in one form or another consistent with the three-phase delays described by Thaddeus and Maine. Most of the participants (16) experienced two delays and 15 experienced second-phase delay, which was always coupled with the other; nine participants experienced delay while at the hospital. None of the participants experienced all three delays. Most decisions to seek health care when labor was complicated were made by mothers-in-law and traditional birth attendants. All but two delivered stillborn babies.Conclusion: Testimonies by women in our study suggest the complexity of the journey to developing fistula. Poverty, illiteracy, inaccessible health facilities, negligence, lack of male involvement in childbirth issues, and shortage of staff together conspire to fistula formation. To prevent new cases of OF in Malawi, the above mentioned issues need to be addressed, more importantly, increasing access to skilled attendance at birth and emergency obstetric care and promoting girls’ education to increase their financial autonomy and decision-making power about their reproductive lives. Also men need to be educated and be involved in maternal and women’s reproductive health issues to help them make informed decisions when their spouses end up with a complicated labor or delivery. Keywords: childbirth experience, delays, obstetric fistula, Malawi